The State and Problems of the Tourism Industry in Ukraine and Transcarpathia - Berghauer Sándor; Fodor Gyula; Бергхауер Олександр; Фодор Дюло (РВВ МДУ, 2021)
Abstract. The settings for the development of the tourism industry in Ukraine in general and the Transcarpathian region in particular have been impregnated by features that are characteristic for long time for the Ukrainian economic and social environment as well as the peculiarities of tourism itself. The understanding and transparency of tourism development in Ukraine in accordance with the internationally accepted and common tourism knowledge is impossible without the revelation of these specific features.
Keywords: tourism industry; economic transition; investment environment; tourism policy; legal background; tourist traffic